Stress concentration factor for thin-walled structures having corrosion damages - Астанін, В. В.; Бородачов, М. М.; Сирота, Н. О. (Proceedings of National Aviation University (archive), 2021)
The paper considers determination of stress concentration factors, in the thin-walled structure elements with local corrosion damages, whish have significant depth (up to 60% of the wall thickness). At that effect of stress concentration and flexural strain is considered simultaneously